What is religion? An African understanding - Beyers, Jaco (HTS teologiese studies, 2010)
Western thought has influenced the way that religion is understood. Western philosophy supported the separation between the sacred and the profane. Modernism, focusing on human rationality, reduced religion to a set of correctly formulated dogmas and doctrines. Western thought, dominated by Christianity, created a hierarchical structure of world religions through a theology of religions. Can an African understanding of religion make a contribution to the understanding of what religion is? Such a question requires an African understanding of religion, as well as an understanding of African religion. From an African perspective, religion emphasises the human effort to systematise, in society, the continuation of a religious experience relevant to a specific context. Tradition, expressed in rituals and ethics, becomes the social expression of these religious experiences. African religion tends not to differentiate the transcendental from the earthly. African scholars do not present one unified understanding of religion. Some scholars would even argue that an African understanding is nothing more than an internalised form of Western perspectives. To characterise African Traditional Religion as a separate type of religion minimises the contribution that an African understanding can make to religion.